2004
DOI: 10.1177/1077801204267377
|View full text |Cite
|
Sign up to set email alerts
|

“I Couldn’t go Anywhere”

Abstract: The authors examine the narratives of 24 substance-addicted welfare recipients to understand how their neighborhoods provide a particular context for substance abuse, violence, and social isolation. The authors also examine the relationships among substance abuse, violence, and social isolation. Overall, these narratives indicate that place of residence influences one’s social networks and exposure to drugs, which subsequently influence women’s experiences with substance abuse and domestic violence. The author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(7 citation statements)
references
References 52 publications
0
5
0
2
Order By: Relevance
“…Those approaches included assessing lack of social support (49,50), lack of emotional or informational support (42), lack of practical, emotional, and critical support (47), number of friends or frequency of contacts (44), as well as membership in social networks and levels of social interaction (15). Having one of those indicators alone does not necessarily indicate being socially isolated, but when combined with other factors, such as unemployment, poverty, or drug use, they may provide an adequate indicator of social isolation (34). These findings are consistent with most recent studies which suggest that increasing feelings of isolation during the COVID-19 lockdown measures may cause abuse of alcohol, drugs, as well as increased anger and aggression, which may also lead to violence toward the self or others ( 52), such as one's intimate partner (53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those approaches included assessing lack of social support (49,50), lack of emotional or informational support (42), lack of practical, emotional, and critical support (47), number of friends or frequency of contacts (44), as well as membership in social networks and levels of social interaction (15). Having one of those indicators alone does not necessarily indicate being socially isolated, but when combined with other factors, such as unemployment, poverty, or drug use, they may provide an adequate indicator of social isolation (34). These findings are consistent with most recent studies which suggest that increasing feelings of isolation during the COVID-19 lockdown measures may cause abuse of alcohol, drugs, as well as increased anger and aggression, which may also lead to violence toward the self or others ( 52), such as one's intimate partner (53).…”
Section: Discussionmentioning
confidence: 99%
“…This association can be found in terms of coercive control, which implicates that social isolation can be caused by IPV through controlling several aspects of the victim's everyday life, such as limiting social contacts or access to professional help (33). On the other hand, studies investigated IPV against women found that many victims experienced physical and emotional aspects of IPV as a consequence of being forced into isolation by the perpetrator, suggesting that IPV could be a possible outcome of social and geographical isolation (34).…”
Section: Social and Geographical Isolation And Ipvmentioning
confidence: 99%
“…This study is significant because gender violence is considered a key source of inequality when addressing the treatment of drug addiction in women (Jessell et al, 2022) and it has been shown that gender violence has multiple bidirectional relationships with drugabuse related problems which should be addressed together (James et al, 2004;Lorvick et al, 2014).…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…Social integration breakdowns contribute to feelings of isolation and danger related to IPV perpetration (House & Khan, 1985). James et al (2004) identify limited social networks, impoverished neighborhood conditions, and limited mobility as factors that enhance social isolation, which complicates a victim's ability to leave an abusive relationship and may lead to IPH. Also, IPV victims are more likely to have smaller social networks, reducing access to adequate social support (Katerndahl et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on existing literature indicating exposure reducing effects between DV resources and IPH (Dugan et al, 2003; Reckdenwald & Parker, 2012), it is hypothesized that the presence of DV resources will be negatively related to female victim IPH. Likewise, following research indicating limited mobility and social isolation interfere with the ability to leave a violent relationship (James et al, 2004), it is hypothesized that accessibility via transportation will also be negatively related to female victim IPH.…”
Section: Literature Reviewmentioning
confidence: 99%